Conocimiento de zoonosis en operarios tamberos de la provincia de Santa Fe, Argentina - Koziol, E.E. (2016)
Dairy operators are risk of becoming infected by diseases transmitted by cattle. The aim of this study was to assess the awareness of zoonosis and risk perceptions of dairy operators in the province of Santa Fe on zoonosis to which they are exposed and their association with the use of elements for personal protection. A survey was carried out on dairy operatos (N= 203) who attended training meetings throughout Santa Fe Province. Data was collected by means of self-administered structured questionnaire. Statistical analysis included ?2, Fisher exact test, Student t test and Spearman correlation coefficient. Brucellosis was the most recognized zoonosis, while leptospirosis had the lowest recognition. Correct answers identifying zoonosis tended to be associated with each other. Vaccination against brucellosis was perceived as a risky activity, while handling dead animals was considered a low risk activity. The use of protective elements was independent of risk perception. The workers said they had not received formal training on work hazards to which they are exposed. Our results showed that dairy operators had low awareness of zoonosis and their means of transmission, a worrying situation given their daily exposure to these hazards.